Exome sequence analysis identifies a homozygous, pathogenic, frameshift variant in the MAN2B1 gene underlying clinical variant of α-mannosidosis - Hashmi, Jamil Amjad; Latif, Muhammad; Balahmar, Reham M.; Ali, Muhammad Zeeshan; Alfadhli, Fatima; Khan, Muzammil Ahmad; Basit, Sulman (Frontiers in Genetics, 2024)
Background: α-mannosidosis (MAN) is a rare genetic condition that segregates in an autosomal recessive manner. Lack of lysosomal alpha-mannosidase is the underlying cause of the disease.Symptoms of the disease gradually worsen with the age. Newborns are usually asymptomatic, however, some cases are reported with either congenital ankle equinus or hydrocephalus during the first year. Primary symptoms are characterized by immune deficiency, hearing loss, skeletal abnormalities, progressive mental, motor and speech functions' impairment followed by facial asymmetry.We studied two Saudi families (A and B) with bilateral moderate hearing loss (family A) and clubfoot with glaucoma (family B). Clinical diagnosis was not reached based on phenotype of patients. Therefore, hypothesis-free whole exome sequencing (WES) was performed on DNA samples from affected individuals of both the families, followed by Sanger sequencing and segregation analysis to validate the segregation of the identified variant. Furthermore, 3D protein modelling was performed to determine the in-silico effects of the identified variant on the protein structure and function.: Re-examination of clinical features revealed that the patients in family A have speech delay and hearing impairment along with craniostenosis, whereas the patients from family B have only clubfoot and glaucoma. WES identified a well known pathogenic homozygous frameshift variant (NM_000528.4: c.2402dupG; p.S802fs*129) in MAN2B1 in both the families. Sanger sequencing confirmed the segregation of the variant with the disease phenotype in both the families. 3D structural modeling of the MAN2B1 protein revealed significant changes in the tertiary structure of the mutant protein, which would affect enzyme function. This report presents a new case where partial and novel α-mannosidosis phenotypes are associated with a MAN2B1 gene pathogenic variant. Conclusion: Patients in both the families have manifested peculiar set of clinical symptoms associated with α-mannosidosis. Family A manifested partial clinical symptoms missing several characteristic features like intellectual disability, dysmorphic features, neurological and abdominal manifestations, whereas family B has no reported clinical symptoms related to α-mannosidosis except the novel symptoms including club foot and glaucoma which has never been reported